Speech By YBhg Tan Sri At The Visit To The International Institute Of Health Sciences, Sri Lanka - Anuwar Ali, (Open University Malaysia (OUM), 2013)

(untitled)
A text-of-speech by YBhg Tan Sri Anuwar Ali, President/Vice-Chancellor of Open University Malaysia (OUM) at the visit to the International Institute Of Health Sciences, Sri Lanka at 10.00am, 31st January 2013